Implementasi Bimbingan dan Konseling Pendidikan di MI Soebono Mantofani, Tanggerang Selatan - Rahmawati Al-Nur, Widya; Ziyaan Izaanatulhaqq; Dafa Afiah (Jurnal Kependidikan, 2025)
Guidance and Counseling in elementary schools play an important role, especially in shaping students' character and personality. Guidance and counseling at MI Soebono Mantofani are conducted by class teachers using group guidance methods aimed at shaping students' personalities and preventing bullying that often occurs among MI students. This research is a qualitative study using a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. This research is focused on class 5C MI Soebono Manttofani Tangerang Selatan. The research results regarding the implementation of guidance and counseling at MI Soebono Mantofani indicate that the guidance and counseling were carried out by the homeroom teacher of class 5C. The stages of implementation are problem identification, making an approach, core activities (strengthening students' self-worth, collaboration and positive interaction, evaluation and follow-up), as well as the impact and evaluation of Guidance and Counseling. The suggestion for the future is that the implementation of Guidance and Counseling should be more systematically documented in school records.